2021
DOI: 10.1186/s13613-021-00941-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of IL-6 inhibitors in patients with COVID-19 pneumonia: a systematic review and meta-analysis of multicentre, randomized trials

Abstract: Purpose COVID-19 is characterized by dysregulated immune response, respiratory failure and a relevant mortality rate among hospitalized patients. Interleukin-6 (IL-6) is involved in COVID-19-associated cytokine storm, and several trials investigated whether its inhibition could improve patients’ outcome. We performed a meta-analysis of randomized trials (RCT) to test this hypothesis. Materials and methods Two independent investigators searched PubM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 63 publications
1
17
0
3
Order By: Relevance
“…Additionally, IL-6 was also reported as an independent predictor of ICU admission [95]. The results of this meta-analysis were also in line with a previous meta-analysis of RCTs that presented a reduction in the incidence of intubation in COVID-19 patients receiving IL-6 inhibitors [96].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Additionally, IL-6 was also reported as an independent predictor of ICU admission [95]. The results of this meta-analysis were also in line with a previous meta-analysis of RCTs that presented a reduction in the incidence of intubation in COVID-19 patients receiving IL-6 inhibitors [96].…”
Section: Discussionsupporting
confidence: 88%
“…Another study recorded that the mean IL-6 levels were 2.9 times higher in complicated COVID-19 patients compared with uncomplicated COVID-19 patients [97]. A meta-analysis of RCTs reported a decreased incidence of death in COVID-19 patients receiving IL-6 inhibitors [96].…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that tocilizumab improves treatment outcomes in enrolled patients about 10 days after symptoms onset and within 48 h from hospital admission, with a moderate to severe illness [ 16 , 17 , 19 ]. A recent meta-analysis also suggested that administration of tocilizumab within 10 days after symptom onset could reduce mortality and the need for intubation [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…These are humanized monoclonal antibodies approved by the United States Food and Drug Administration (FDA) for use in rheumatoid arthritis, giant cell arteritis, and cytokine release syndrome [ 9 , 10 , 45 , 46 ]. Multiple trials have evaluated IL-6 antagonists for treatment of COVID-19, finding an overall reduction in 28-day mortality [ [45] , [46] , [47] , [48] , [49] , [50] , [51] ]. The REMAP-CAP study evaluated tocilizumab or sarilumab versus standard of care within the first 24 h of ICU admission for COVID-19 patients requiring either respiratory support (invasive and non-invasive mechanical ventilation including HFNC >30 L/min and FiO2 > 0.4) or cardiovascular support (vasopressor or inotrope infusion) [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are concerns of superinfection, hepatotoxicity, thrombocytopenia, and leukopenia with IL-6 antagonists, but current data suggest no significant difference in adverse events when compared with placebo or standard care [ 9 , 10 , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] ]. The WHO recommends patients with severe or critical COVID-19 infections should be given both steroids and IL-6 antagonists simultaneously [ 9 ].…”
Section: Discussionmentioning
confidence: 99%